Társadalmi átrétegződés és szociális-politikai identifikáció (Szociológiai Szemle, 2024)
Transformation theories tend to relate the consolidation of democratic institutions to the process of embourgoisement and the establishment of a strong middle class in East Central European societies. As to the Hungarian case, one can observe in the press, but even in scientific discussions, the coexistence of two more or less contrasting views. Putting an emphasis on the restructuration of ownership (the spread of private property in the wake of the political changes), one of these schools of thought has stated the emergence of a broad well-established middle class. While as a rule not entering a direct confrontation, representatives of the other approach have spoken of polarization tendencies, the (relative or absolute) deprivation of wide strata, including a considerable part of middle class losing ground, as well. The issue has been dealt with by subtler terms at the scientific scene bringing in a distinction between the objective and subjective aspects of the problem. Those claiming the growth of middle class must by now face hard evidence of opposite tendencies (such as the significant shrinkage in the last decade of households possessing discretional incomes). Not denying these facts some authors still argue for a broadening middle class consciousness on the basis of heightened social aspirations and weakening ties toward working class among lower strata, too. It is this frame of reference that we have addressed by presenting some findings of our recent survey of class identification.